Synthesis and characterization of ZnxCd1−xO a/polymer junction for photovoltaic application - Mushtaq, Umer (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
This thesis describes the synthesis and characterization of polycrystalline ZnxCd1-xO/Polymer based photovoltaic cells. Photovoltaic cell holds great demand for use as economically and environmental friendly viable renewable energy resources. For these purposes thin films of blend zinc-cadmium oxide ZnxCd1-xO and PEO - Chitosan were prepared, studied and investigated. The growth of ZnxCd1-xO nanorods was synthesized from a chloride electrolytic bath by a single step electrodeposition process for applications in photo-electronics. Ternary single-phase ZnxCd1-xO semiconductor thin films of polycrystalline nature were electrodeposited on indium doped tin oxide conductive glass substrates by varying zinc and cadmium concentration from 10% - 90% in an electrolytic bath. The aim is to produce high surface area blend zinc-cadmium oxide thin films in order to obtain n-type working electrode for photovoltaic cell. A platinum plate was used as counter electrode; the polyethylene oxide blend with chitosan was synthesized by solution casting technique. The role of PEO - Chitosan (ionic conductor) is to host electron transfer. X ray diffraction analysis of blend zinc-cadmium oxide ZnxCd1-xO confirms a hexagonal wurtzite structure of (200) planes for zinc oxide having grain size of 37 nm and a cubic structure of (111) planes for cadmium oxide was also found. The (200) peak is due to the cadmium doping. From the field emission scanning electron microscopy analysis, the synthesized ZnxCd1-xO nanorods have uniform hexagonal crystallographic planes, and each face of regular hexagonal nanorod is about 63.6 nm. Remarkably, the energy band gap was tailored and was shifted from 2.75 eV to 3.3 eV due to the direct modulation of band gap caused by Cadmium substitution, revealed by ultra violet visible spectroscopy. Temperature is deemed as a key parameter for the formation of different morphologies of ZnxCd1-xO nanostructures. ZnxCd1-xO hexagonal nanorods thin film on indium tin oxide is used as window layer or top layer and PEO - chitosan is used as absorbing electrode or bottom layer. These two electrodes or layers were assembled to form photovoltaic cell and hence to produce energy by absorbing the sunlight. The junction formed by assembling two electrodes synthesized early is schottky junction that has been put forward as a potential low-cost alternative to the widely used silicon based photovoltaic cells. I-V characterization for ZnxCd1-xO/ polymer based photovoltaic cells showed efficiency of 1.702%. However, the cost effectiveness is due to the electrodeposition technique in producing ZnxCd1-xO nanorods as working electrode and solution casting technique to produce polymer as absorbing electrode.